2013
DOI: 10.1148/rg.335115170
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Signal Intensity Characteristics of Pelvic Recurrence of Rectal Cancer at MR Imaging

Abstract: Magnetic resonance (MR) imaging is becoming the cross-sectional imaging modality of choice for follow-up of patients with previous rectal cancer to diagnose pelvic recurrence and plan for surgery. The authors conducted a retrospective review of MR imaging examinations performed at their institution for evaluation of local recurrence of rectal cancer in 42 patients. Twenty-six patients had undergone rectal anastomosis and 16 had undergone abdominoperineal resection. The mean interval between initial surgery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
0
27
1
5
Order By: Relevance
“…In our study, the specificity , sensitivity and accuracy were about 85.7% , 92,3% , 94.9 % respectively which showed no significant changes from results of Lambregets et al (12) since specificity was 91 % , sensitivity was 100 % and accuracy was 95 % and Sinaei et al (13) (Sensitivity 90% and specificity was 100% ,accuracy was 96 %). Colosio et al (5) (Accuracy up to 99 % , sensitivity up to 100 % and specificity up to 86 %) Grosu et al (14) (Sensitivity 93% and specificity was 91%, accuracy 92 %).…”
Section: Discussioncontrasting
confidence: 44%
“…In our study, the specificity , sensitivity and accuracy were about 85.7% , 92,3% , 94.9 % respectively which showed no significant changes from results of Lambregets et al (12) since specificity was 91 % , sensitivity was 100 % and accuracy was 95 % and Sinaei et al (13) (Sensitivity 90% and specificity was 100% ,accuracy was 96 %). Colosio et al (5) (Accuracy up to 99 % , sensitivity up to 100 % and specificity up to 86 %) Grosu et al (14) (Sensitivity 93% and specificity was 91%, accuracy 92 %).…”
Section: Discussioncontrasting
confidence: 44%
“…Once the tumor reaches the sacral plexus, it can continue to spread within neural structures in a proximal as well as a distal and cause various symptoms in relation to the affected structures, namely, the clinical entity known as neoplastic lumbosacral plexopathy (LSP) (see below). Proximally, it can involve sacral spinal nerves (Boyle et al, 2005;Sinaei et al, 2013) and extend to the lumbar plexus and lumbar spinal nerves (Sinaei et al, 2013) via the lumbosacral trunk (Gierada and Erickson, 1993) as in our cases ( Figs. 1 and 3).…”
Section: Discussionmentioning
confidence: 53%
“…3 and 5). Several other cases of the sciatic nerve (Rao et al, 1982;Gaeta et al, 1988;Kameyama et al, 1993;Beets-Tan et al, 2000;Sinaei et al, 2013) as well as obturator (Gaeta et al, 1988;Tan et al, 2011;Sinaei et al, 2013), pudendal (Gaeta et al, 1988), inferior gluteal, and posterior femoral cutaneous nerve involvement (LaBan et al, 1982) have been reported, which we believe, can also be explained anatomically: either as spread from the infiltrated lumbosacral plexus, as in our cases, or by direct tumorous invasion during their intrapelvic course with subsequent perineural spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We opted to use visual inspection rather than an absolute standardized uptake value to define a hypermetabolic focus. Pelvic recurrence was classified according to the location of the lesion [ 4 ].…”
Section: Methodsmentioning
confidence: 99%